Does the buck stop with the bugs?: an overview of microbial dysbiosis in rheumatoid arthritis. (19th September 2015) - Sandhya, Pulukool; Danda, Debashish; Sharma, Disha; Scaria, Vinod
Abstract: The human body is an environmental niche which is home to diverse co‐habiting microbes collectively referred as the human microbiome. Recent years have seen the in‐depth characterization of the human microbiome and associations with diseases. Linking of the composition or number of the human microbiota with diseases and traits date back to the original work of Elie Metchnikoff. Recent advances in genomic technologies have opened up finer details and dynamics of this new science with higher precision. Microbe‐rheumatoid arthritis connection, largely related to the gut and oral microbiomes, has showed up as a result – apart from several other earlier, well‐studied candidate autoimmune diseases. Although evidence favouring roles of specific microbial species, including Porphyromonas, Prevotella and Leptotricha, has become clearer, mechanistic insights still continue to be enigmatic. Manipulating the microbes by traditional dietary modifications, probiotics, and antibiotics and by currently employed disease‐modifying agents seems to modulate the disease process and its progression. In the present review, we appraise the existing information as well as the gaps in knowledge in this challenging field. We also discuss the future directions for potential clinical applications, including prevention and management of rheumatoid arthritis using microbial modifications.